Stimulation of non-histone chromosomal protein synthesis in simian virus 40-infected simian cells. - Iida, H (1975)
The pattern of synthesis of non-histone chromosomal proteins in simian virus (SV) 40-infected African green monkey kidney cells was analyzed by polyacryl-amide gel electrophoresis to see whether the changes in chromosomal protein metabolism are involved in the viral-induced synthesis of cellular DNA and mRNA. During the prereplicative phase of infection, the rate of histone synthesis was decreased until 15 h postinfection, whereas that of non-histone protein synthesis was increased after 5 h postinfection and reached a maximum at 10 to 15 h postinfection when viral-induced synthesis of cellular DNA and mRNA began to be observed. Stimulation of non-histone protein synthesis was also observed in the infected cells treated with cytosine arabinoside and was dependent on the multiplicity of infection. Stimulation occurred in almost all species of non-histone proteins. These results suggest that the stimulation of non-histone protein synthesis is caused by an early SV40 function and occurs prior to the viral-induced synthesis of cellular DNA and mRNA. During the replicative phase of infection, a marked increase in the rate of synthesis was observed in the non-histone proteins with molecular weights of about 48,000, 35,000, and 23,000, which were subsequently found to be SV40 capsid proteins.